MHD Flow with Slip Effects and Temperature-dependent Heat Source in a Viscous Incompressible Fluid Confined between a Long Vertical Wavy Wall and a Parallel Flat Wall - Taneja, Rajeev; Jain, N.C. (Defence Science Journal, 2004)
This study examines the problem of an MHD free convection flow in the presence of a temperaturedependent heat source in a viscous incompressible fluid between a long vertical wavy wall and a parallel flat wall with constant heatflux and slip flow boundary condition. A uniform magnetic field is assumed to be applied perpendicular to the walls. It is assumed that the flow consists of two parts; amean part and aperturbedpart. Expressions for the zeroth-order and first-order velocity, temperature, skin friction, and Nusselt number at the wal lr ;ire obtained. The effects of different parameters entering into the problem, viz., free convection parameter, magnetic parameter, and heat source parameter on the zeroth-order and first-order velocity fields, temperature field, skin friction, and Nusselt number at the walls are shown graphically and discussed numerically,